Rules governing the efficiency and polarity of loading a tracking clamp protein onto DNA: determinants of enhancement in bacteriophage T4 late transcription. - Sanders, G M (1995)
The bacteriophage T4 DNA polymerase accessory proteins confer processivity and high speed on replicative DNA chain elongation: the gene 45 protein, gp45, tracks along DNA and serves as the sliding clamp of the viral DNA polymerase; the gene 44/62 protein complex, gp44/62, is an ATP-dependent loading enzyme that mounts gp45 on DNA. Gp45 also activates T4 late transcription. Transcriptional enhancement by gp45 requires a particular orientation that is imposed by gp44/62 at the DNA loading site. Loading and orienting gp45 on DNA, tracking along DNA and interaction with RNA polymerase have been analyzed by measuring transcriptional activation. The efficiency of loading gp45 at different DNA structures and the resulting transcriptional activation have been compared, and sources of interference with transcriptional activation have been examined. All observations are compatible with a mechanism in which the loading enzyme recognizes the polarity of single-stranded DNA and imposes a corresponding polarity of DNA entry on gp45. Primer-template junctions are the most efficient DNA loading sites for gp45 and can generate very rapid opening at promoters that are located at a distance of > 1 kbp. In contrast, gp45 does not track efficiently across single-stranded DNA.